High Stakes without the Stakes: Positioning Music Educators amid Teacher Evaluation Reforms. (March 2022) - Shaw, Ryan
Teacher-focused accountability started to ramp up in the United States in 2007–2010 as the focus of accountability shifted from schools to individual teachers. Since that time, there has been a remarkable amount of change to the way that teachers are evaluated, and music teachers have been placed squarely under the microscope of accountability. In this article, I focus on high-stakes teacher evaluation (HSTE), a collection of reforms that are among the most hot-button issues of the past ten years. I argue that despite the intentions of these reforms, they were mostly "high stakes" only on paper. However, HSTE reforms have been far from inconsequential, with numerous negative effects on teachers. I first review the origins and logic of the HSTE reforms and discuss how music teachers were considered in such policy conversations. I then demonstrate how the reforms were mostly characterized by bluster and incomplete/subverted implementation, and I attempt to explain the reasons for the sputtering of HSTE. Finally, I discuss the negative consequences of HSTE and offer recommendations for music teachers as they navigate teacher evaluation in the future.